Supply-demand Balance Prediction of Water Resources in Hebei Province Based on System Dynamics - WANG Jianquan; QIN Huanhuan; HUANG Lixiang; ZHU Shiyi (Renmin Zhujiang)
To ease the long-term contradiction between the supply and demand of water resources in Hebei Province, the system dynamics method was used to construct a supply-demand model of water resources in Hebei Province. Based on factors in the studied area including economic development level and water resources utilization, five different development scenarios were designed (status quo continuation scenario W1, economic development scenario W2, water conservation scenario W3, pollution control scenario W4, and coordinated development scenario W5). Water demand in Hebei Province from 2022 to 2050 was thus predicted. According to the results, ①the total water demand shows an increasing trend under the five scenarios, with average values of 23.947, 25.851, 21.553, 23.947 and 23.295 billion m3 respectively; ②all five scenarios are in a state of water shortage, with an average shortage degree of 0.243 8, 0.302 6, 0.137 5, 0.146 7 and 0.129 0 respectively; ③ the average value of agricultural water demand, under the five scenarios, accounts for the largest proportion of the average value of total water demand, with 46.57%, 43.14%, 45.72%, 46.57%, and 43.85% respectively. Therefore, agricultural water use efficiency improvement plays an important role in reducing water consumption.